Protective effect of adenosine triphosphate against sunitinib-related skin damage in rats - Yildirim, N.; Karatas, A.; Cengiz, M.; Onalan, E.; Yazici, G. N.; Sunar, M.; Suleyman, H. (Sage Publications Ltd, 2020)
Cutaneous side effects associated with sunitinib use are a major problem in patients receiving cancer treatment. The aim of this study was to investigate the protective effect of adenosine triphosphate (ATP) against possible skin damage resulting from sunitinib use in rats. Thirty Albino Winstar rats were divided into the following three groups: healthy controls (HCs,n= 10), sunitinib (SUN,n= 10), and sunitinib + ATP (SAT,n= 10). ATP was injected intraperitoneally at a dose of 2 mg/kg. One hour subsequent to the administration of ATP and 0.9% NaCl, the SAT and SUN groups were orally administered a dose of 25 mg/kg sunitinib to the stomach. Macroscopic evaluation of the skin indicated lower levels of skin damage in the SAT group than in the SUN group. As an indicator of oxidative stress, malondialdehyde (MDA), total oxidant status (TOS), and oxidative stress index (OSI) levels were significantly higher in the SUN group than in the HC group, while total glutathione (tGSH) and total antioxidant status (TAS) levels were significantly lower. However, MDA, TOS, and OSI levels were significantly lower in the SAT group than in the SUN group, while tGSH and TAS levels were significantly higher. Histopathological examination revealed keratin plugs with edema, vasopathology, and inflammatory cell infiltration in the SUN group. The SAT group showed less necrotic epithelium, keratin plugs, edema, and vasopathology than the SUN group. ATP can be effective in preventing skin damage caused by sunitinib use by reducing oxidative stress.
Keywords: Sunitinib; cutaneous side effects; oxidative stress; adenosine triphosphate; protective effect